Über lineare inhomogene System von Differential-Differenzengleichungen - Gylys, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Гилис. О неоднородной линейной системе дифференциально-разностных уравнений A. Gylys. Tiesinės nehomogeninės diferencialinių-skirtuminių lygčių sistemos klausimu